Clinical utility of next‐generation sequencing in the diagnosis of hereditary haemolytic anaemias. (12th June 2016) - Agarwal, Archana M.; Nussenzveig, Roberto H.; Reading, Noel S.; Patel, Jay L.; Sangle, Nikhil; Salama, Mohamed E.; Prchal, Josef T.; Perkins, Sherrie L; Yaish, Hassan M.; Christensen, Robert D.
Summary: Hereditary haemolytic anaemias are genetically and phenotypically heterogeneous disorders characterized by increased red cell destruction, with consequences ranging from innocuous to severe life‐threatening anaemia. Diagnostic laboratories endeavour to assist clinicians reach the exact patient diagnosis by using tests principally based on morphological and biochemical techniques. However, these routine studies may be inconclusive, particularly in newborn infants and when transfusions have recently been administered. Large numbers and size of the potentially involved genes also impose a practical challenge for molecular diagnosis using routine sequencing approaches. To overcome these diagnostic shortcomings, we have utilized next‐generation sequencing to provide a high‐throughput, highly sensitive assay. We developed a panel interrogating 28 genes encoding cytoskeletal proteins and enzymes with sequencing coverage of the coding regions, splice site junctions, deep intronic and regulatory regions. We then evaluated 19 samples, including infants with unexplained extreme hyperbilirubinaemia and patients with transfusion‐dependent haemolytic anaemia. Where possible, inheritance patterns of pathogenic mutations were determined by sequencing of immediate relatives. We conclude that this next‐generation sequencing panel could be a cost‐effective approach to molecular diagnosis of hereditary haemolytic anaemia, especially when the family history is uninformative or when routine laboratory testing fails to identify the causative haemolytic process.